The interdisciplinary management of Severe burns in pregnancy. Issue 2 (October 2017) - Wallner, Christoph; Kern, Peter; Teig, Norbert; Lehnhardt, Marcus; Behr, Björn
Highlights: Severe burns in pregnant patients demand an interdisciplinary treatment approach. Enzymatic debridement is a treatment option for burn wounds in pregnant patients. A caesarean delivery in late pregnancy can facilitate a better therapy for wounds. Abstract: Background: Severe burns in pregnant women present an exceedingly challenging situation due to the limitation in therapeutic options including pain management and operative care. Case: We present a 30 years old patient, 38th week of pregnancy, who suffered a full thickness skin burns in 20% total body surface area and an inhalation trauma. In a Level-1 trauma center an interdisciplinary team of plastic surgeons, neonatologists and gynecologists was organized to deliver best patient care. Conclusion: This case presents a challenging situation with an intubated analgosedated pregnant woman, limiting treatment options. On admission a prompt cesarean delivery was performed to guard the unborn child. To shorten the hospital stay, a novel Bromelain based enzymatic debridement was performed on the full thickness burn wounds with immediate skin grafting.